2021
DOI: 10.1136/sextrans-2020-054846
|View full text |Cite
|
Sign up to set email alerts
|

Going beyond ‘regular and casual’: development of a classification of sexual partner types to enhance partner notification for STIs

Abstract: ObjectivesTo develop a classification of sexual partner types for use in partner notification (PN) for STIs.MethodsA four-step process: (1) an iterative synthesis of five sources of evidence: scoping review of social and health sciences literature on partner types; analysis of relationship types in dating apps; systematic review of PN intervention content; and review of PN guidelines; qualitative interviews with public, patients and health professionals to generate an initial comprehensive classification; (2) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…The LUSTRUM team is already using the partnership classification in data collection and analysis of an RCT of PN [ 11 ]. The underpinning primary and secondary research describing the process of development is published elsewhere [ 12 ].…”
Section: Development Of Updated Partner Notification Outcome Measuresmentioning
confidence: 99%
“…The LUSTRUM team is already using the partnership classification in data collection and analysis of an RCT of PN [ 11 ]. The underpinning primary and secondary research describing the process of development is published elsewhere [ 12 ].…”
Section: Development Of Updated Partner Notification Outcome Measuresmentioning
confidence: 99%
“…There are challenges in reporting partnership type and cohabitation status, especially during a period when circumstances may change, as shown by people reporting IPCOH, with some defining themselves as single and others as in a new/casual relationship. Partnership typologies used in clinical practice or research 27 are less relevant when examining IPCOH as these are used to determine sexual risk, rather than COVID-19 risk behaviours, and do not emphasise cohabitation status.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many actors, actions and settings involved in the whole process of PN (see Flowers et al, in preparation) here, we only focus on the "gateway step" in which GBMSM notify their partners of their exposure to an STI. Elsewhere we report on a more comprehensive approach to developing an intervention to improve PN (Flowers et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting however that it is likely these digitally mediated ways of meeting are more likely to facilitate PN than meeting through public sex environments for example (e.g., see Flowers et al, 1999;Flowers et al, 2000) PN and partner type When diagnosed with an STI, people's abilities to contact sexual partners and the motivation to do so relate to the kind of relationship that connects them. Working with a range of evidence sources, to assist with considering the tailoring of PN approaches to relational contexts, we developed a typology of sexual partner types ('Established partner', 'New partner', 'Occasional partner', 'One-off partner' and 'Sex worker') (Estcourt et al, 2021). Our evidence synthesis suggested that PN was most challenging with 'one-off partners'.…”
Section: Pn and Msmmentioning
confidence: 99%
See 1 more Smart Citation